Successful Reintegration and Mental Health: An Examination of Gender Differences Among Reentering Offenders - Bakken, Nicholas W. (Criminal justice and behavior, 2018)
Men and women exiting the correctional system represent a population at high risk for mental health problems, and the body of research on the mental health needs of former prisoners is growing. These mental health problems pose challenges for individuals at every stage of the criminal justice process, from arrest to incarceration to reentry and reintegration. This article examines the mental health status and gender differences among a sample of 352 men and women leaving confinement and the role that mental health problems played in shaping their reentry outcomes using data collected between 2002 and 2005. In the year after leaving prison, men and women with mental health problems reported worse health indicators and less satisfactory social factors, such as employment, housing, and family support. The article concludes with a discussion of recommendations for improved policy and practice for assisting former prisoners with mental health problems during reintegration.